Pre-procedural use of thrombopoietin-receptor agonists in cirrhosis and severe thrombocytopenia: A systematic review and meta-analysis. Issue 11 (November 2021) - Rose, Peter D.; Au, Minnie; Woodman, Richard J.; Tee, Derrick; Chinnaratha, Mohamad A
Abstract: Background: Severe thrombocytopenia in cirrhosis can preclude invasive procedures. Platelet transfusion is recommended if platelet count pre-procedure is potential alternative to platelet transfusion is thrombopoietin-receptor (TPO) agonists. Aim: Evaluate TPO-agonist efficacy and safety in cirrhotic patients with severe thrombocytopenia undergoing invasive procedures. Methods: Randomized control trials (RCT) from electronic reference databases were searched from inception till December 2019. PRISMA guidelines were followed. Primary outcome was platelet transfusion avoidance. Secondary outcomes were weighted mean difference (WMD) in platelet count from baseline to pre-procedure and rates of major adverse events (AE). Pooled Odds Ratio (OR) were estimated using a random-effects model. Results: Six RCTs with 1, 229 patients were included. All studies had low risk of bias. Compared with placebo, those treated with TPO-agonists had a pooled OR of 0.12(0.08-0.17), P<0.01 for platelet transfusion avoidance, and WMD in platelet count (x10 3 /µL) of 35.6(28.6-42.7), P<0.01. Major AE did not differ between groups [Pooled OR: 0.87(0.47–1.62), P=0.66]. Conclusion: Compared to placebo, TPO-agonists used in cirrhotic patients with severe thrombocytopenia prior to elective invasive procedures had 88% reduced odds of requiring peri-procedural platelet transfusion and increased platelet count pre-procedure, with no difference in AE rates.